Evalutaion of immune responses of a recombinant theileria parva 2 antigen fused with a cell penetrating peptide from human immunodeficiency virus-1. - Tinega, A.N. (Kenyatta University, 2008)
East Coast fever (ECF) is a tick-borne protozoal disease of cattle confined to Eastern, Central and Southern Africa. It is caused by an intracellular apicomplexan parasite, Theileria parva which is transmitted by the brown ear tick Rhipicephalus appendiculatus. The disease threatens the livelihoods of many African livestock farmers and it constitutes a major constraint to dairy industries. Control of ECF is mainly dependent on the use of acaricides, drugs and a live vaccine. However increasing prevalence of acaricide resistance in tick populations coupled with the high cost and cold chain requirements of the live vaccine has necessitated search for alternative control measures. Efforts are being focused on the development of a cheap and easy-to-deliver vaccine based on components of the parasite. Immunity to T. parva is associated with major histocompatibility complex class I (MHC-I) restricted CD8+ cytotoxic T lymphocytes (CTL) that kill lymphocytes infected with the schizont stage of the parasite. A number of T. parva vaccine candidate antigens have been identified that are the targets of CTL from immune cattle. Vaccination of cattle with recombinant DNA and viral vectors expressing these antigens have been shown to induce protective CD8+ CTL responses in a proportion of cattle. However an effective delivery strategy that consistently induces protective CTL responses remains to be identified. This study was aimed at determining whether fusing a cell penetrating peptide (CPP) from human immunodeficiency virus-1 trans-acting activator of transcription (HIV-1; TAT) to CTL target antigens from T. parva vaccine candidate antigen (Tp2) enhances the stimulation of bovine CD8+ CTL responses in vitro and induction of murine CD8+ CTL responses in vivo. Bovine in vitro experiments were carried out to assess the stimulation of CTL responses and a spectrum of MHC-I biochemical inhibitors were used to investigate the MHC-I processing and presentation pathway utilised. An experiment was conducted in thirty mice to assess the ability of CPP-antigen fusion proteins to stimulate CTL responses in vivo. Western blot and IFN-y ELISpot assays were used to evaluate antibody and CD8+ CTL responses respectively. Analysis of variance was used to compare the differences in immune responses between the experimental groups. The study has shown that the induction of bovine T. parva 2 (Tp2) specific CD8+ T cell responses in vitro can be achieved by antigen delivery to bovine antigen presenting cells (APC) by trans-acting activator of transcription- cell penetrating peptide (TAT-CPP). Interestingly, immunisation of mice with Tp2 protein induced CD8+ T cell IFN-'Y responses that were greater in magnitude compared to Tp2-CPP while immunisation with Tp2-CPP fusion protein induced greater antigen-specific antibody responses compared to Tp2-protein. The study has further shown that Tp2 CPP enhanced the induction of CD8+ T cell responses in vitro but failed to enhance significant CD8+ T cell responses in vivo. This area will require further investigation to explain these unexpected results. This study has contributed to the understanding and development of vaccination strategies for the delivery of CTL targeted T. parva antigens.